Bridge scour monitoring by coupling factor between reader and Tag antennas of RFID system - Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (International Journal of GEOMATE, 2015)
Bridge scour is an erosion which remove s stream bed or bank material from bridge foundation due to flowing of water. Too much bridge scour is risky for the bridge foundation and cause s sudden bridge to collapse without any warning. It implements significant impacts on the traveling public safety as well as the economy of the country . A number of parameters are associated with scour, thus different types of sensors are required to measur e the individual affecting factor. A complex and expensive data logging from sensor and electronic communication system s are used to monitor the br idge scour in real - time to ensure the integrity of bridge structure. A high frequency band (13.56MHz) radio f requenc y identification (RFID) system ha s been proposed and that has been validated by simulation using PSpice software for the direct scour monitoring scheme , which is simple and low - cost . A number of passive RFID tag s have been piled surrounding the brid ge foundation which is continuously detected by the FRID reader . The erosion of the river bed carries out the RFID tag from nearby the bridge structure . A s a result , the RFID reader can directly detect the absence of the tag s as well as the amount of the s couring. Since, the design structure of the RFID system is simple , it is highly robust and easy to implement. The system can easily be implement ed with an existing bridge structure and a wireless telemetry can be used to send the real - time data from the pr oposed system to a desktop computer in the monitoring lab